Kajian Kepemimpinan Path Goal Theory Studi Literature Review - Lusy Rahmawati; Nur Aini; Firman Agung Pradana; Mochammad Isa Ansori (International Forum of Researchers and Lecturers, 2023)
This study aims to explain leadership path goal theory. Literature study is used as a method in research. The data is taken, collected, and analyzed from books and scientific journals that have similar topics, then made into writings and conclusions. The results of the study show that using path goal leadership can increase employee motivation. The results applied with the application of the path goal leadership style can increase employee motivation. Path-goal theory recognizes four leadership behaviors for increasing subordinate motivation. The four path-goal leadership styles that serve to provide structure and reward to subordinates are directive, supportive, participatory, and achievement-oriented.